PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PELAKSANAAN TUGAS KOMISI PEMILIHAN UMUM PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DI INDONESIA TAHUN 2019 - Suryanto, Amri; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a problem that arises when observations made by researchers, namely the demonstration of the University of Riau students on the implementation of the task of the general election commission. Students who are referred to as intellectuals who are considered critical of the political conditions in Indonesia, of course have a deep perception or view of the implementation of the tasks of the General Election Commission, given the General Election Commission as the organizer of the General Election of the President and Vice President and Board members simultaneously in 2019. . The formulation of the problem in this research is What is the University of Riau Student's Perception of the Implementation of the Election Commission's Duties in the Election of President and Vice President in Indonesia in 2019? The purpose of this research is to find out how the University of Riau Students' Perceptions of the Implementation of the Election Commission's Duties in the Election of President and Vice President in Indonesia in 2019. This research was conducted at the University of Riau in May to November 2019. This study used a descriptive methodquantitative. The population in this study amounted to 31,478 who are active students of Riau University. The sample in this study was taken using a purposive sampling technique with a total of 100 people from all students. The results showed that the University of Riau Students' perception of the implementation of the general election commission tasks in the election of President and Vice President in Indonesia in 2019 was in the category of